2016
DOI: 10.1055/s-0035-1569455
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic Differentiation of Lateral Elbow Pain

Abstract: Lateral elbow pain is often attributed to degenerative or posttraumatic impairment of the common extensor tendon. Ultrasonography assesses the soft tissue structures of the lateral elbow, allowing the differentiation between various underlying processes, including angiofibroblastic degeneration, hyaline degeneration, and inflammation, and exclusion of other possible causes of pain such as posterior interosseous and lateral antebrachial nerve compression. Furthermore, the real-time imaging nature of ultrasonogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 50 publications
1
10
0
Order By: Relevance
“…Typical findings in patients with LE are focal areas with decreased echogenicity, thickening, and alteration of the typical fibrillar echostructure. Although the typical US findings of the disease described in the literature include increased vascularity observed in the power/color Doppler study, we almost never observed increased vascularity, except for patients with spondylarthritis, which is also indicated by other authors [13,16] the extensor carpi radialis brevis of CEO are affected [14,17].…”
Section: Us Findings In Lesupporting
confidence: 73%
See 1 more Smart Citation
“…Typical findings in patients with LE are focal areas with decreased echogenicity, thickening, and alteration of the typical fibrillar echostructure. Although the typical US findings of the disease described in the literature include increased vascularity observed in the power/color Doppler study, we almost never observed increased vascularity, except for patients with spondylarthritis, which is also indicated by other authors [13,16] the extensor carpi radialis brevis of CEO are affected [14,17].…”
Section: Us Findings In Lesupporting
confidence: 73%
“…In longstanding disease, degenerative processes such as advanced partial or even complete tears may appear (fig 7), sometimes resulting in the formation of calcification (fig 8) [17].…”
Section: (Fig 6) Commonly Deep and Anterior Fibers Ofmentioning
confidence: 99%
“…Firstly, the ECRB is the central tendon involved in a degenerative process of LET, and in this study, we only considered the exhaustive descriptions and analysis for degenerative ultrasound findings in the interior of this tendon. However, most of the existing publications describe the relation between LET and different anatomical aspects 40 or other adjacent tissues such as nerve, ligaments, muscles, bone structures or more tendons 41 and even other health conditions that are not unique to the alteration of the origin of the wrist extensors. Secondly, researchers have proposed that the tendon pathogenesis model is continuous, arguing that there is a 3-state transition from an initial stage characterized by reactive tendinopathy, a second disruptive stage, and finally, a third degenerative stage.…”
Section: Discussionmentioning
confidence: 99%
“…4) [37]. During tendon healing, there may be intratendinous infiltration of inflammatory cells and neovascularization [38].…”
Section: Elbowmentioning
confidence: 99%